Fetal movement frequency and the effect of associated perinatal factors: Multicenter study. Issue 2 (April 2019) - Koshida, Shigeki; Ono, Tetsuo; Tsuji, Shunichiro; Murakami, Takashi; Arima, Hisatomi; Takahashi, Kentaro
Abstract: Background: Decreased fetal movements are associated with adverse perinatal outcomes, including stillbirth. Delayed maternal visits to a health care provider after perceiving decreased fetal movements are frequently observed in stillbirths. Informing pregnant women of the normal range of fetal movement frequency is essential in their earlier visits in order to prevent stillbirth. Aim: To investigate the fetal movement frequency in late pregnancy and the effects of associated perinatal factors. Methods: This prospective multicenter study was conducted in 20 obstetric facilities in our region of Japan. A total of 2337 pregnant women were asked to record the time it took to perceive 10 fetal movements by the modified 'count to 10' method every day from 34 weeks of gestation until delivery. Findings: The 90th percentile of the time for the maternal perception of 10 fetal movements was 18–29 min, with a gradually increasing trend toward the end of pregnancy. The numbers of both pregnant women giving birth after 39 weeks' gestation and infants with a birth weight exceeding 3000 g were significantly higher in mothers who took ≥30 min to count 10 fetal movements than in those who took <30 min. Conclusion: The maternal perception time of fetal movements shows a gradually increasing trend within 30 min for 10 fetal movements by the modified 'count to 10' method. Informing pregnant women of the normal range of the fetal movement count time will help improve the maternal recognition of decreased fetal movements, which might prevent fetal death in late pregnancy.